THE EFFECT OF EMOTIONAL INTELLIGENCE ON RESILIENCE WITH SELF-EFFICACY AS MEDIATION: A STUDY ON GENERATION Z - Olivia Winda Ony Panjaitan; Dian Mutiasari (ZILLZELL MEDIA PRIMA, 2024)
Currently, resilience is an ability that is expected to be possessed by every individual because with resilience a person can rise from the problems faced in a productive way. Resilience itself is influenced by how well a person manages emotions and is able to be calm, and how confident the individual is in his ability to solve the problems faced. The purpose of this study was to determine the effect of emotional intelligence on resilience with self-efficacy as mediation. The research respondents were 96 Gen Z respondents. The research instrument was an online questionnaire. Analysis technique with SEM-PLS. The results showed that self-efficacy perfectly mediates the effect of emotional intelligence on individual resilience.